STUDI ALIRAN FLUIDA MANIFESTASI PANAS BUMI DESA DIWAK DAN DESA DEREKAN, KECAMATAN BERGAS, KABUPATEN SEMARANG MENGGUNAKAN METODE TAHANAN JENIS 3D. - Hotlan Simbolon; Udi Harmoko; Gatot Yulianto; Sugeng Widada; Yusuf D. H.; Sahid Sahid (Youngster Physics Journal, 2015)
This research use geolistric method that aims to analize the system of manifestation of fluida distribution geothermal on Diwak, Derekan Central Java, based on measurement of geolistric 3-D with pole - pole configuration, has been done. Data processing is performed using software Res3dinv and surfer which results in a horizontal and vertical cross-section. The results of the interpretation of 2D processed by software rockwork to obtain 3-D cross-section. The results showed that the measurement point 1, the direction of the fluid flow toward the east. Measurement point 2, the direction of flow of the fluid toward the northwest, the fluid flow direction to both of the points towards Lutung river. Keywords : Fluida, pole-pole konfiguration, Diwak, Derakan